Efectos del enriquecimiento con N y P sobre la comunidad del fitoplancton en microcosmos de un embalse tropical (La Mariposa, Venezuela) - González, Ernesto J; Ortaz, Mario (Revista de Biología Tropical, 1998)
The effect of nutrient enrichment (N and P) on the phytoplankton community of La Mariposa reservoir (Venezuela) was studied. Polyethylene bags (microcosms) were filled with 10 I offiltered epilimnetic water of the reservoir, and enriched with different nutrient proportions, simulating an eutrophication process. Chlorophyll ’a’, lotal nitrogen, total phosphorus, and phytoplankton abundance were determined. There was an increase in phytoplankton abundance because of nutrient enrichment, specially when both nutrients were present. After (he experiments, Cryptophyta, Euglenophyta, and Pyrrophyta dissappeared from the microcosms, whereas Chlorophyta and Cyanobacteria increased. Numeric proportions of diatoms decreased at higher nitrogen concentration. Although the results obtained with microcosm experiments could be limited in ecological significance, they permit an useful approach to the natural situation.’